A note on a class of Banach algebra-valued polynomials - Sin-Ei Takahasi; Osamu Hatori; Keiichi Watanabe; Takeshi Miura (International Journal of Mathematics and Mathematical Sciences)
Let F be a Banach algebra. We give a necessary and sufficient condition for F to be finite dimensional, in terms of finite type n-homogeneous F-valued polynomials.